2001
DOI: 10.1111/j.1095-8649.2001.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for selective angling of introduced trout and their hybrids in a stocked brown trout population

Abstract: Comparisons of the genetic composition of brown trout Salmo trutta captured by anglers and by electrofishing based on three diagnostic microsatellite loci provided strong evidence that angling is selective in a stocked brown trout population. At two sites, anglers caught significantly younger trout and proportionally more introduced hatchery trout and hybrids than were observed in electrofishing surveys. Selective angling, in combination with a small legal catch size, may have considerably eliminated introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 41 publications
5
38
2
Order By: Relevance
“…Although this contradicts some previous findings in which fishing was negatively correlated with hatchery admixture (García-Marín et al 1998), potentially because of anglers being more efficient at catching hatchery fish than wild fish (Mezzera and Largiadèr 2001;Champigneulle and Cachera 2003), it does support the hypothesis proposed by Evans and Willox (1991). These authors showed, through modeling, that fishing preferentially removes large, highly fecund wild and hatchery fish alike, but while wild fish have only one source of replacement (natural recruitment), hatchery fish are potentially replaced by both natural recruitment and further stocking events.…”
Section: Anthropogenic Correlates Of Hatchery-wild Admixturecontrasting
confidence: 81%
See 1 more Smart Citation
“…Although this contradicts some previous findings in which fishing was negatively correlated with hatchery admixture (García-Marín et al 1998), potentially because of anglers being more efficient at catching hatchery fish than wild fish (Mezzera and Largiadèr 2001;Champigneulle and Cachera 2003), it does support the hypothesis proposed by Evans and Willox (1991). These authors showed, through modeling, that fishing preferentially removes large, highly fecund wild and hatchery fish alike, but while wild fish have only one source of replacement (natural recruitment), hatchery fish are potentially replaced by both natural recruitment and further stocking events.…”
Section: Anthropogenic Correlates Of Hatchery-wild Admixturecontrasting
confidence: 81%
“…Recent studies have found that the extent of admixture from stocking can be correlated with a species' life history (Utter 2000), stocking intensity (Almodovar et al 2006), fishing pressure (García-Marín et al 1998;Mezzera and Largiadèr 2001), population size (Hansen et al 2009), abiotic factors (Rasmussen et al 2010;Marie et al 2012), and human activities . Few of these studies have rigorously examined the relative influence of multiple habitat and anthropogenic factors in driving variation in hatchery-wild admixture among populations (but see Marie et al 2012), though such investigations may bear practical results.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations from Hardy-Weinberg equilibrium (HWE) were tested using the exact probability test of Guo & Thompson (1992) available in GENEPOP 3.4 (Raymond & Rousset 1995). Mezzera & Largiadèr 2001). These tests used a Markov chain method (1000 dememorisation steps, 100 batches and 1000 iterations per batch).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…  cohorts (Mezzera, 2000). In another study, there were strong indications that selective angling may be the main factor for a decrease of these genotypes at this stage (Mezzera & Largiadèr, 2001).…”
Section: Difference In Introgression and Apparent Admixture Between Amentioning
confidence: 92%
“…All observed alleles were assigned to two distinct allele classes, a ' hatchery specific ', and a ' native specific ' allele class, respectively. The assignment and pooling of alleles at microsatellite loci was carried out as described in Mezzera & Largiadèr (2001). Allele frequencies are given in Appendices I and II.…”
Section: Discrimination Between Alien and Native Allelesmentioning
confidence: 99%